Critique of Western Educational Philosophy, the Urgency of Islamization, and Its Implementation - Armizi, Armizi; Liriwati, Fahrina Yustiasari; Asfami, Atih (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study aims to critically examine Western educational philosophy theories and highlight the urgency of Islamization of educational knowledge as a response to the value crisis caused by secular approaches in modern education systems. Western educational philosophy, dominated by rationalism, empiricism, pragmatism, and existentialism, tends to reduce the human being to a rational or material entity, neglecting the spiritual dimension and the ultimate purpose of life. In the context of the Muslim world, the uncritical adoption of Western educational theories can lead to value disorientation, secularization of educational goals, and the weakening of students’ Islamic identity. Therefore, the Islamization of educational knowledge is an urgent necessity to establish an educational paradigm rooted in divine revelation, integrating both rational ('aqlī) and scriptural (naqlī) knowledge, and oriented toward the development of the ideal human being (insān kāmil). This research employs a qualitative approach using library research methods, analyzing the thoughts of key Western educational thinkers and the concept of Islamization as articulated by Muslim scholars. The findings indicate that Islamization is not merely a process of purifying the curriculum from secular elements, but an epistemological project aimed at restoring education to its essential nature—as a means of tazkiyah (soul purification) and the cultivation of adab (proper conduct). The practical implications of educational Islamization call for curriculum reform, teacher training, and evaluation systems grounded in Islamic values in a holistic and sustainable manner.